ANALYSIS OF THE FACTORS AFFECTING THE FINANCIAL PERFORMANCE OF INSURANCE COMPANIES LISTED ON THE PALESTINE STOCK EXCHANGE - Barakat, Firas S. Q.; Hussein, Jawad; Mahmoud, Oroubah A. R.; Bayyoud, Mohammed (Indian Journal of Finance and Banking, 2022)
The objective of this study was to investigate the factors affecting the financial performance of insurance companies in Palestine. The entire study population was targeted at 7 insurance companies listed on the Palestine Exchange for the period between 2010 and 2019. The researchers used multiple linear regression analysis to create two models that represent the financial performance; the study adopted two models for measuring financial performance, the first model measuring financial performance by return on assets, and the other measuring financial performance by return on equity. The results showed a positive and statistically significant impact on the solvency margin, the state’s legal system, the size of the board of directors, and the size of the company on the return on assets. There is a negative, statistically significant impact on each of the claims loss ratios, the dependence on the four major auditing firms, and the ownership of board members on the return on assets. The reliability of reinsurance and the audit committee did not show a statistically significant effect on the return on assets. The results showed a positive, statistically significant impact of the solvency margin and company size on the return on equity. The results indicate a negative, statistically significant impact of both the claims loss ratio and the Audit Committee on the return on equity. Reinsurance dependent, dependence on the four major auditing companies, the state’s legal system, the size of the board of directors, and the ownership of board members have no significant effect on the return on equity. The study recommends that insurance companies in Palestine should comply with the required margin of money, which was set by the Palestinian Capital Market Authority at 150%. JEL Classification Codes: G32, G22, G34, H54.